2017
DOI: 10.17344/acsi.2017.3534
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption of Cr(III) from Aqueous Solution using Borax Sludge

Abstract: Borax sludge is the waste produced by a trommel sieve in the borax production process and is used as an adsorbent for Cr(III) removal. The effects of various parameters, including pH, initial Cr(III) concentration and contact time were investigated for batch adsorption of Cr(III). The experimental results obtained were applied to different adsorption isotherms and kinetic models. The results indicated that the Temkin isotherm (R 2 = 0.9749) was most suitable to explain the adsorption characteristics of borax s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 29 publications
(41 reference statements)
1
5
0
Order By: Relevance
“…The experimental data show a linearity that is compatible with the Langmuir isotherm, indicating that the Langmuir mathematical model most faithfully describes the adsorption equilibrium of BPA. Similar results were obtained in a different study [31].…”
Section: Adsorption Equilibrium 321 Adsorption Isotherm For Different...supporting
confidence: 91%
“…The experimental data show a linearity that is compatible with the Langmuir isotherm, indicating that the Langmuir mathematical model most faithfully describes the adsorption equilibrium of BPA. Similar results were obtained in a different study [31].…”
Section: Adsorption Equilibrium 321 Adsorption Isotherm For Different...supporting
confidence: 91%
“…A comparison between the adsorption capacities (q m ) values of different adsorbents reported in the literature and that of RPG for adsorption of Cd 2+ and Cr 3+ ions (Table 3). It may be shown that q m values differ widely for different adsorbents [76, 77, 78, 79, 80, 81, 82, 83, 84, 85, 86, 87, 88, 89, 90, 91, 92]. Comparison of q m values also stated that RPG exhibited a reasonable capacity for adsorption of Cd 2+ and Cr 3+ ions from aqueous solutions.…”
Section: Resultsmentioning
confidence: 95%
“…Several factors affect the efficiency of heavy metal adsorption. The initial concentration of adsorbate influences so that in the initial stage of the adsorption process the rate, in general, is high, decreasing until steady state is reached [33]. The adsorption time affects the process in different ways depending on the adsorbate particles size, the amount of active preferential sites on the surface, as well as changes in the chemical composition on the surface of the adsorbent material [34].…”
Section: Introductionmentioning
confidence: 99%